2023
DOI: 10.20473/juxta.v14i12023.12-16
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Chronic Kidney Disease (CKD) in Type 2 Diabetes Mellitus (DM) Patients at Dr. Soetomo General Academic Hospital, Surabaya

Abstract: Highlights:1. The highest risk was a history of hypertension, followed by a history of low HDL levels.2. Patients with type 2 DM at Dr. Soetomo General Academic Hospital, Surabaya, had a greater risk of developing CKD for patients with a history of hypertension (3.801 times higher) and patients with a history of low HDL (3.356 times higher). AbstractIntroduction: Type 2 diabetes mellitus (DM), categorized as a non-communicable disease, has become a global health concern. This study aimed to identify the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…All of these processes increase triglyceride levels, which correlate with microangiopathic complications of diabetic kidney diseas. but, the complete mechanism is not yet known (Sutadji et al, 2023). However, these complications are likely to increase during the pandemic of COVID-19, which is most likely caused by COVID-19 infection of the ACE-2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…All of these processes increase triglyceride levels, which correlate with microangiopathic complications of diabetic kidney diseas. but, the complete mechanism is not yet known (Sutadji et al, 2023). However, these complications are likely to increase during the pandemic of COVID-19, which is most likely caused by COVID-19 infection of the ACE-2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should note that approximately 50% of older patients present their first kidney stone episode at admission to emergency rooms, and the risk increases with the presence of diabetes mellitus (Arampatzis et al 2012). A study even found that type 2 diabetes increased the risk of chronic kidney disease, especially in patients with high blood pressure and low high-density lipoprotein (Sutadji et al 2023).…”
Section: Discussionmentioning
confidence: 99%